Pelatihan Penyusunan Bahan Ajar Online Interaktif untuk Meningkatkan Kompetensi Profesional Guru - Erni Mariana; Kusuma Wardany; Ayang Kinasih; Ummi Rosyidah; Siti Qomariyah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
Problems regarding the lack of teacher readiness and understanding of the importance of compiling teaching materials according to needs, the benefits of teaching materials in preparing learning tools, and implementing learning. Regarding the abilities, skills, and skills of the teacher, of course in this case talking about competence. a very important competency possessed by a teacher so that the learning process can run smoothly and optimally optimizing learning in the classroom. The purpose of the community service activities carried out at SMA in Metro is to improve the professional competence of teachers. This activity is carried out in three forms, namely outreach, training and mentoring, and evaluation. As for the stages of activity in the form of dissemination of the use of Microsoft Power Point in the preparation of interactive online teaching materials, training and assistance in the preparation of interactive online teaching materials with Microsoft Power Point, as well as evaluation of activities to find out the increase in the professional competence of high school teachers in Metro which is marked by an increase in professional competence marked by an increase in the ability teachers in developing material creatively and interestingly so that teachers are able to utilize information and communication technology to produce interactive online teaching material products.